Isotopic constraints on active nitrification in a eutrophic artificially oxygenated lake: Implications for nitrate regeneration and nitrous oxide production - Alessandra Mazzoli; Claudia Frey; Cameron M. Callbeck; Jakob Zopfi; Teresa Einzmann; Chiara Piantoni; Tim J. Paulus; Moritz F. Lehmann (Limnology and Oceanography, 2026)
Nitrification is a key process in the aquatic nitrogen (N) cycle, but its products, nitrate (NO 3 − ) and nitrous oxide (N 2 O), contribute to eutrophication and greenhouse gas emissions, particularly in eutrophic lakes. Variations in in‐lake N cycling and N 2 O production pathways, as a function of seasonality and artificial oxygenation, remain poorly understood. We investigated nitrification in the artificially oxygenated eutrophic Lake Baldegg, by analyzing NO 3 − and N 2 O concentrations and isotope ratios, and measuring ammonium oxidation rates via 15 N tracer incubations over one year. An N isotope mass‐balance model revealed that nitrification sustained only 5.3 ± 0.7% of total NO 3 − consumption in the epilimnion, where external N loadings were influential, and considerably more in the hypolimnion (81.6 ± 18.5%) during stratification. Dual NO 3 − isotope signatures (Δδ 18 O : Δδ 15 N ~ 1.5–1.73) and associated negative NO 3 − isotope anomalies confirmed epilimnetic nitrification, though external inputs partly obscured this signal. During stratification, relatively high hypolimnetic nitrification rates correlated with organic matter export, and seemed linked to sediment resuspension and artificial oxygenation. While sedimentary denitrification/DNRA dominated hypolimnetic NO 3 − reduction (with negligible effects on δ 15 N‐NO 3 − and δ 18 O‐NO 3 − ), transient suboxic conditions enabled water column denitrification during stratification (24.1–30.2% of the total hypolimnetic denitrification). High N 2 O isotope site‐preference values (30–35‰) confirmed hypolimnetic ammonium oxidation as the main N 2 O production pathway. During winter overturn, N 2 O transport from the hypolimnion caused epilimnetic N 2 O oversaturation and atmospheric emissions up to 3.52 μ mol m −2 d −1 . Comparison with other lakes suggests that artificial oxygenation enhances N turnover, manifesting in greater ambient N 2 O backgrounds and fluxes to the atmosphere.

Marine monitors: Land-based citizen science observations show AIS data underrepresents coastal vessel traffic co-occurring with marine mammals - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Carole Davis; Bernard Siddle; Debbie Cole; Sarah MacDonald-Taylor; Peter Gulliver; Rebecca Olaleye; Juliane Lehmann; et al. (Biological Conservation, 2025)

AIS data underrepresents vessel traffic around coastal Scotland - Emily Hague; Alice Walters; Anna Moscrop; Emma Steel; Katie Dyke; Lauren Hartny-Mills; Alison Lomax; Rebecca Dudley; Pippa Garrard; Jenny Hampson; Sadie Gorvett; Hannah Lightley; et al. (Marine Policy, 2025)

Dynamic modulations of effective brain connectivity associated with postural instability during multi-joint compound movement on compliant surface - Tim Lehmann; Anton Visser; Tim Havers; Daniel Büchel; Jochen Baumeister (Experimental Brain Research, 2025)
Random fluctuations in somatosensory signals affect the ability of effectively coordinating multimodal information pertaining to the postural state during movement. Therefore, this study aimed to investigate the impact of a compliant surface on cortico-cortical causal information flow during multi-joint compound movements. Fifteen healthy adults (7 female / 8 male, 25.9 ± 4.0 years) performed 5 × 20 repetitions of bodyweight squats on firm and compliant surface. Motor behavior was quantified by center of pressure (CoP) displacements, hip movement and the root mean square of the rectus femoris activity. Using source space analysis, renormalized partial directed coherence (rPDC) computed subject-level multivariate effective brain connectivity of sensorimotor nodes. Bootstrap statistics revealed significantly decreased medio-lateral CoP displacement ( p < 0.001), significantly increased velocity of medio-lateral hip motion ( p < 0.001) as well as significantly lower rectus femoris activity ( p < 0.01) in the compliant surface condition. On the cortical level, rPDC showed significantly modulated information flow in theta and beta frequencies for fronto-parietal edges ( p < 0.01) only during the concentric phase of the movement. The compliant surface led to increased difficulties controlling hip but not center of pressure motion in the medio-lateral plane. Moreover, a decreased activation of the prime movers accompanied by modulations of effective brain connectivity among fronto-central nodes may point to altered demands on sensorimotor information processing in presence of sensory noise when performing bodyweight squats on compliant surface. Further studies are needed to evaluate a potential benefit for athletic and clinical populations.

Reliable electrocortical dynamics of target-directed pass-kicks - Daghan Piskin; Daniel Büchel; Tim Lehmann; Jochen Baumeister (Cognitive Neurodynamics, 2024)
Football is one of the most played sports in the world and kicking with adequate accuracy increases the likelihood of winning a competition. Although studies with different target-directed movements underline the role of distinctive cortical activity on superior accuracy, little is known about cortical dynamics associated with kicking. Mobile electroencephalography is a popular tool to investigate cortical modulations during movement, however, inherent and artefact-related pitfalls may obscure the reliability of functional sources and their activity. The purpose of this study was therefore to describe consistent cortical dynamics underlying target-directed pass-kicks based on test–retest reliability estimates. Eleven participants performed a target-directed kicking task at two different sessions within one week. Electroencephalography was recorded using a 65-channel mobile system and behavioural data were collected including motion range, acceleration and accuracy performance. Functional sources were identified using independent component analysis and clustered in two steps with the components of first and subsequently both sessions. Reliability estimates of event-related spectral perturbations were computed pixel-wise for participants contributing with components of both sessions. The parieto-occipital and frontal clusters were reproducible for the same majority of the sample at both sessions. Their activity showed consistent alpha desyhronization and theta sychnronisation patterns with substantial reliability estimates revealing visual and attentional demands in different phases of kicking. The findings of our study reveal prominent cortical demands during the execution of a target-directed kick which may be considered in practical implementations and provide promising academic prospects in the comprehension and investigation of cortical activity associated with target-directed movements.

Why has farming in Europe changed? A farmers’ perspective on the development since the 1960s - Franziska Mohr; Vasco Diogo; Julian Helfenstein; Niels Debonne; Thymios Dimopoulos; Wenche Dramstad; Maria García-Martín; Józef Hernik; Felix Herzog; Thanasis Kizos; Angela Lausch; Livia Lehmann; et al. (Regional Environmental Change, 2023)
Farming in Europe has been the scene of several important socio-economic and environmental developments and crises throughout the last century. Therefore, an understanding of the historical driving forces of farm change helps identifying potentials for navigating future pathways of agricultural development. However, long-term driving forces have so far been studied, e.g. in anecdotal local case studies or in systematic literature reviews, which often lack context dependency. In this study, we bridged local and continental scales by conducting 123 oral history interviews (OHIs) with elderly farmers across 13 study sites in 10 European countries. We applied a driving forces framework to systematically analyse the OHIs. We find that the most prevalent driving forces were the introduction of new technologies, developments in agricultural markets that pushed farmers for farm size enlargement and technological optimisation, agricultural policies, but also cultural aspects such as cooperation and intergenerational arrangements. However, we find considerable heterogeneity in the specific influence of individual driving forces across the study sites, implying that generic assumptions about the dynamics and impacts of European agricultural change drivers hold limited explanatory power on the local scale. Our results suggest that site-specific factors and their historical development will need to be considered when addressing the future of agriculture in Europe in a scientific or policy context.

Somatosensory perturbations influence cortical activity associated with single-limb balance performance - David A. Sherman; Tim Lehmann; Jochen Baumeister; Dustin R. Grooms; Grant E. Norte (Experimental Brain Research, 2022)

Stance leg and surface stability modulate cortical activity during human single leg stance - Daniel Büchel; Tim Lehmann; Sarah Ullrich; John Cockcroft; Quinette Louw; Jochen Baumeister (Experimental Brain Research, 2021)
Mobile Electroencephalography (EEG) provides insights into cortical contributions to postural control. Although changes in theta (4–8 Hz) and alpha frequency power (8–12 Hz) were shown to reflect attentional and sensorimotor processing during balance tasks, information about the effect of stance leg on cortical processing related to postural control is lacking. Therefore, the aim was to examine patterns of cortical activity during single-leg stance with varying surface stability. EEG and force plate data from 21 healthy males (22.43 ± 2.23 years) was recorded during unipedal stance (left/right) on a stable and unstable surface. Using source-space analysis, power spectral density was analyzed in the theta, alpha-1 (8–10 Hz) and alpha-2 (10–12 Hz) frequency bands. Repeated measures ANOVA with the factors leg and surface stability revealed significant interaction effects in the left ( p = 0.045, η p 2 = 0.13) and right motor clusters ( F = 16.156; p = 0.001, η p 2 = 0.41). Furthermore, significant main effects for surface stability were observed for the fronto-central cluster (theta), left and right motor (alpha-1), as well as for the right parieto-occipital cluster (alpha-1/alpha-2). Leg dependent changes in alpha-2 power may indicate lateralized patterns of cortical processing in motor areas during single-leg stance. Future studies may therefore consider lateralized patterns of cortical activity for the interpretation of postural deficiencies in unilateral lower limb injuries.

Balance task difficulty affects postural sway and cortical activity in healthy adolescents - Arnd Gebel; Tim Lehmann; Urs Granacher (Experimental Brain Research, 2020)
Electroencephalographic (EEG) research indicates changes in adults’ low frequency bands of frontoparietal brain areas executing different balance tasks with increasing postural demands. However, this issue is unsolved for adolescents when performing the same balance task with increasing difficulty. Therefore, we examined the effects of a progressively increasing balance task difficulty on balance performance and brain activity in adolescents. Thirteen healthy adolescents aged 16–17 year performed tests in bipedal upright stance on a balance board with six progressively increasing levels of task difficulty. Postural sway and cortical activity were recorded simultaneously using a pressure sensitive measuring system and EEG. The power spectrum was analyzed for theta (4–7 Hz) and alpha-2 (10–12 Hz) frequency bands in pre-defined frontal, central, and parietal clusters of electrocortical sources. Repeated measures analysis of variance (rmANOVA) showed a significant main effect of task difficulty for postural sway ( p < 0.001; d = 6.36). Concomitantly, the power spectrum changed in frontal, bilateral central, and bilateral parietal clusters. RmANOVAs revealed significant main effects of task difficulty for theta band power in the frontal ( p < 0.001, d = 1.80) and both central clusters (left: p < 0.001, d = 1.49; right: p < 0.001, d = 1.42) as well as for alpha-2 band power in both parietal clusters (left: p < 0.001, d = 1.39; right: p < 0.001, d = 1.05) and in the central right cluster ( p = 0.005, d = 0.92). Increases in theta band power (frontal, central) and decreases in alpha-2 power (central, parietal) with increasing balance task difficulty may reflect increased attentional processes and/or error monitoring as well as increased sensory information processing due to increasing postural demands. In general, our findings are mostly in agreement with studies conducted in adults. Similar to adult studies, our data with adolescents indicated the involvement of frontoparietal brain areas in the regulation of postural control. In addition, we detected that activity of selected brain areas (e.g., bilateral central) changed with increasing postural demands.

A novel germline POLE mutation causes an early onset cancer prone syndrome mimicking constitutional mismatch repair deficiency - Katharina Wimmer; Andreas Beilken; Rainer Nustede; Tim Ripperger; Britta Lamottke; Benno Ure; Diana Steinmann; Tanja Reineke-Plaass; Ulrich Lehmann; Johannes Zschocke; Laura Valle; Christine Fauth; et al. (Familial Cancer, 2017)